2018
DOI: 10.4103/jiaps.jiaps_58_17
|View full text |Cite
|
Sign up to set email alerts
|

A randomized control trial comparing outcome after stented and nonstented Anderson-Hynes dismembered pyeloplasty

Abstract: Aim:The aim of the study was to compare the efficacy and postoperative complications of stented and nonstented open pediatric dismembered pyeloplasty for ureteropelvic junction (UPJ) obstruction.Settings and Design:A balanced, parallel group, prospective randomized controlled trial comparing stented and nonstented Anderson-Hynes Dismembered Pyeloplasty.Subjects and Methods:It included 42 children who required Anderson-Hynes dismembered pyeloplasty for UPJ obstruction (UPJO). Patients were randomized into stent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…A randomized controlled trial of stented versus non-stented OP in 42 pediatric patients demonstrated no differences in surgical outcomes at 3-month nuclear renal scan. As expected, they noted significantly increased levels of post-operative pain and dysuria in the stented cohort which resolved upon stent removal (11). Similar level of evidence is lacking in the adult population.…”
Section: Discussionsupporting
confidence: 58%
“…A randomized controlled trial of stented versus non-stented OP in 42 pediatric patients demonstrated no differences in surgical outcomes at 3-month nuclear renal scan. As expected, they noted significantly increased levels of post-operative pain and dysuria in the stented cohort which resolved upon stent removal (11). Similar level of evidence is lacking in the adult population.…”
Section: Discussionsupporting
confidence: 58%
“…This could help to release the stress on the newly formed anastomosis ( 23 ). The DJ stent and external stent were the main management of anastomosis drainage after pyeloplasty, and each measure had its advantages and disadvantages ( 24 , 25 ). The major shortcoming of the DJ stent was that patients, especially infants, needed to undergo second general anesthesia when withdrawing it.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported positive results that are consistent with our results. [21][22][23][24][25] Recently, Nagdeve et al 26 concluded that double-Jstented patients were more symptomatic than unstented patients in the postoperative period, but no significant difference was identified. Considering the relatively low expense and advantages in follow-up for double-J stents, we still suggest double-J stent placement during LP in pediatric patients with UPJO as a safe, feasible, and beneficial method.…”
Section: Discussionmentioning
confidence: 99%